A política cultural da França no Brasil entre 1920 e 1940: o direito e o avesso das missões universitárias - Suppo, Hugo (Revista de História, 2000)
This is a study of the actions undertaken by professor Georges Dumas, a true mentor of the French cultural policy in Brazil. French university lecturers sent to Brazil were the pivot of a strategy based on the use of the French cultural influence over Brazilian elites, as an instrument of political propaganda generating cultural dependence and repercussions at the economic level.